60 Years Later - Testing Kirkpatrick's 4-Level Evaluation Model on an Extra-Occupational Master Program - Bauer, Moritz; Göhlich, Michael (Journal of Education and Human Development, 2020)
This paper investigates the relationships between the evaluation levels in Kirkpatrick's (supposedly) hierarchically constructed 4-level model. Although this evaluation model is still regarded as the most popular and widespread, there are contradictory findings in the scientific discourse regarding the effects the individual evaluation levels have on each other. The present research thus contributes to sharpening the widely used evaluation model. The study is based on a quantitative questionnaire assessing the four levels of the model – reaction, learning, (learning-)transfer and career-success. The questionnaire was completed by a total of 88 alumni of an extra-occupational part-time Master's program in the field of organizational and personnel development. The data analysis using simple and multiple linear regressions shows the hierarchical structure of the model, as each evaluation level determines its subsequent level. This article thus confirms Kirkpatrick's modelling, first published 60 years ago, and contributes to a clearer understanding of the individual evaluation levels
Keywords: evaluation; evaluation model; 4-level model; Kirkpatrick